2018
DOI: 10.22409/geographia2017.v19i41.a13823
|View full text |Cite
|
Sign up to set email alerts
|

Solos Frágeis Do Parque Nacional Da Serra Da Capivara, Piauí

Abstract: Resumo: O Parque Nacional da Serra da Capivara (PNSC) tem alguns dos sítios arqueológicos mais importantes das Américas. A área onde os solos foram amostrados corresponde ao Parque Nacional da Serra da Capivara (PNSC) e uma área tampão de 10km no entorno de seus limites oficiais, no sudeste do Piauí. Para a elaboração do presente trabalho foram selecionados solos considerados frágeis, devido ao alto risco de degradação por erosão, formados de diferentes materiais geológicos representativos do PNSC. Todos os so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This fact corroborates the studies carried out by Crepani et al (2008) in the municipality of Gilbués, who observed soil degradation related to the Areado Group, which succeed only in the extreme southern region of the state of Piauí. Some authors relate pelite parent material or high silt contents with soil erodibility (Clemente et al, 2009;Valladares et al, 2018). The test of correlation between observed and predicted variables demonstrated the degree of similarity between maps, highlighting the variables K, silt, sand, and CDW, with R of 0.710, 0.686, 0.696, and 0.537, respectively.…”
Section: Spatial Analysis Of Modeled Attributesmentioning
confidence: 95%
“…This fact corroborates the studies carried out by Crepani et al (2008) in the municipality of Gilbués, who observed soil degradation related to the Areado Group, which succeed only in the extreme southern region of the state of Piauí. Some authors relate pelite parent material or high silt contents with soil erodibility (Clemente et al, 2009;Valladares et al, 2018). The test of correlation between observed and predicted variables demonstrated the degree of similarity between maps, highlighting the variables K, silt, sand, and CDW, with R of 0.710, 0.686, 0.696, and 0.537, respectively.…”
Section: Spatial Analysis Of Modeled Attributesmentioning
confidence: 95%